The Integration of Some Product Advertisements to Prevent the Transmission of Corona Virus: A Study from Linguistic Landscape Approach - Oktavianus, Oktavianus (International Seminar on Austronesian Languages and Literature; Vol 9 No 1 (2021): PROCEEDINGS International Seminar on Austronesian Languages and Literature IX (ISALL IX), 2021)
Until nowadays, it seems that corona virus has a wide impact toward the human life not only in Indonesia but also across the globe. It does not only embody into a nightmare to the health but it also brings about negative effect to the human life toward social, cultural, economic, religious, and political aspects. So massive and systemic are the corona virus impact to the life of the man-kind, so numerous preventive efforts are launched by various parties. One of the interesting things to pay attention to at the moment is the integrating of some product advertisements to the attempt of preventing the transmission of the corona virus. In respect to that, this brief paper is one of the efforts to discuss the unique advertisement integration of several products to the attempt of preventing the virus corona infection. Such advertisements even previously are not related to the virus corona. This study is observed from the linguistic landscape viewpoint. The data of for this study is taken from the one televised on e-media, and social media. The result of the study showed that the product advertisement is related to the body improvement immunity, environmental cleanliness, and the corona virus preventive infection. The language modification is one thing done by the advertisers in order to integrate a number product advertisements into the attempt of preventing the corona virus infection